Transcriptional regulation of stress kinase JNK2 in pro-arrhythmic CaMKIIδ expression in the aged atrium. Issue 5 (19th January 2018) - Gao, Xianlong; Wu, Xiaomin; Yan, Jiajie; Zhang, Jingqun; Zhao, Weiwei; DeMarco, Dominic; Zhang, Yongguo; Bakhos, Mamdouh; Mignery, Gregory; Sun, Jun; Li, Zhenyu; Fill, Michael; et al.
Abstract: Aims: c-jun N-terminal kinase (JNK) is a critical stress response kinase that activates in a wide range of physiological and pathological cellular processes. We recently discovered a pivotal role of JNK in the development of atrial arrhythmias in the aged heart, while cardiac CaMKIIδ, another pro-arrhythmic molecule, was also known to enhance atrial arrhythmogenicity. Here, we aimed to reveal a regulatory role of the stress kinase JNK2 isoform on CaMKIIδ expression. Methods and results: Activated JNK2 leads to increased CaMKIIδ protein expression in aged human and mouse atria, evidenced from the reversal of CaMKIIδ up-regulation in JNK2 inhibitor treated wild-type aged mice. This JNK2 action in CaMKIIδ expression was further confirmed in HL-1 myocytes co-infected with AdMKK7D-JNK2, but not when co-infected with AdMKK7D-JNK1. JNK2-specific inhibition (either by a JNK2 inhibitor or overexpression of inactivated dominant-negative JNK2 (JNK2dn) completely attenuated JNK activator anisomycin-induced CaMKIIδ up-regulation in HL-1 myocytes, whereas overexpression of JNK1dn did not. Moreover, up-regulated CaMKIIδ mRNA along with substantially increased phosphorylation of JNK downstream transcription factor c-jun [but not activating transcription factor2 (ATF2)] were exhibited in both aged atria (humans and mice) and transiently JNK activated HL-1 myocytes. Cross-linked chromatin-immunoprecipitation assays (XChIP) revealed that both c-jun and ATF2 were bound to the CaMKIIδ promoter, but significantly increased binding of c-jun only occurred in the presence of anisomycin and JNK inhibition alleviated this anisomycin-elevated c-jun binding. Mutated CaMKII consensus c-jun binding sites impaired its promoter activity. Enhanced transcriptional activity of CaMKIIδ by anisomycin was also completely reversed to the baseline by either JNK2 siRNA or c-jun siRNA knockdown. Conclusion: JNK2 activation up-regulates CaMKIIδ expression in the aged atrium. This JNK2 regulation in CaMKIIδ expression occurs at the transcription level through the JNK downstream transcription factor c-jun. The discovery of this novel molecular mechanism of JNK2-regulated CaMKII expression sheds new light on possible anti-arrhythmia drug development.